Potential Role of Hsp70 and Activated NK Cells for Prediction of Prognosis in Glioblastoma Patients - Lobinger, Dominik; Gempt, Jens; Sievert, Wolfgang; Barz, Melanie; Schmitt, Sven; Nguyen, Huyen Thie; Stangl, Stefan; Werner, Caroline; Wang, Fei; Wu, Zhiyuan; Fan, Hengyi; Zanth, Hannah; et al. (Frontiers in Molecular Biosciences, 2021)
Despite rapid progress in the treatment of many cancers, glioblastoma remains a devastating disease with dismal prognosis. The aim of this study was to identify chaperone- and immune-related biomarkers to improve prediction of outcome in glioblastoma. Depending on its intra- or extracellular localization the major stress-inducible heat shock protein 70 (Hsp70) fulfills different tasks. In the cytosol Hsp70 interferes with pro-apoptotic signaling pathways and thereby protects tumor cells from programmed cell death. Extracellular Hsp70 together with pro-inflammatory cytokines are reported to stimulate the expression of activatory NK cell receptors, recognizing highly aggressive human tumor cells that present Hsp70 on their cell surface. Therefore, intra-, extracellular and membrane-bound Hsp70 levels were assessed in gliomas together with activatory NK cell receptors. All gliomas were found to be membrane Hsp70-positive and high grade gliomas more frequently show an overexpression of Hsp70 in the nucleus and cytosol. Significantly elevated extracellular Hsp70 levels are detected in glioblastomas with large necrotic areas. Overall survival (OS) is more favorable in patients with low Hsp70 serum levels indicating that a high Hsp70 expression is associated with an unfavorable prognosis. The data provide a first hint that elevated frequencies of activated NK cells at diagnosis might be associated with a better clinical outcome.